Resistance of Pseudomonas pseudomallei to normal human serum bactericidal action - Ismail, Ghazally; Razak, Nyonya; Mohamed, Rahmah; Omar, Othman; Embi, Noor (Wiley, 1988)
The effect of human normal serum (HNS) on Pseudomonas pseudomallei was determined. It is apparent from our data that the organism is resistant to the normal serum bactericidal mechanism. Ancillary experiments to confirm this serum-resistant property of P. pseudomallei were done by examining the effects of growth phase conditions of the bacteria (i.e., logarithmic and stationary phases) and different buffered systems used as diluent in our bactericidal assay. Results obtained showed similar degree of resistance to serum bactericidal killing by 5 strains of the organisms tested. The possible survival advantage of serum-resistant property to P. pseudomallei as bacterial pathogens known to invade the blood stream is discussed.